Kosakata Bahasa Indonesia dan Bahasa Melayu Malaysia dalam “Series Melur untuk Firdaus Season 2” Episode Perdana di Aplikasi Disney Hotstar: Studi Linguistik Kontrastif - Auliana Dwi Rahmah; Imam Baehaqie (Universitas Islam Sumatera Utara, 2026)
Language plays a fundamental role in human interaction as a medium for conveying ideas and information, and its comparative study is addressed within contrastive linguistics. This study investigates the similarities and differences in vocabulary between Indonesian and Malaysian Malay as represented in the series Melur untuk Firdaus Season 2 Episode One, addressing how lexical variations reflect linguistic and cultural distinctions. Employing a qualitative descriptive approach, data were collected using listening and note-taking techniques, including the derivative free listening technique with involved speaking. Data analysis was conducted using the matching and distributional methods, while findings were presented informally. The results reveal 25 instances of Indonesian vocabulary (BBMS) and 6 instances of Malaysian Malay vocabulary (BBMB), highlighting both shared lexical roots and distinctive variations influenced by sociocultural contexts. The study argues that despite structural and historical proximity, the two languages exhibit meaningful lexical divergences that shape comprehension and communication. These findings contribute to the enrichment of contrastive linguistic studies and provide insights into cross-linguistic understanding in media contexts.